Taming The Wild Card for Mobile Payment - Salajegheh, Mastooreh; Priyantha, Bodhi; Liu, Jie (Microsoft Technical Report, 2013)
Mobile wallets promise to allow people to easily manage their accounts and to carry less cards. However, the slow adoption of contactless point of sales (POS) terminals by merchants limits the potential of Near-Field Communication (NFC) based payment devices. In this paper, we discuss Wild Card, a secure and backward compatible way to make mobile payment through conventional magnetic stripe based POS terminals. The device resembles a traditional credit card in its physical dimensions and stays in the phone case. It can be programmatically set by a NFC-enabled mobile phone to any card number that the user owns. The key technologies that enables Wild Cards are a fully programmable magnetic stripe, an energy harvesting system that allow the card to be charged and programmed by the phone through NFC, and a security mechanism that makes card information resilient to attacks on mobile devices. With a prototype, we evaluate the feasibility of Wild Cards in terms of functionality and energy budget.